2014
DOI: 10.2106/jbjs.m.01288
|View full text |Cite
|
Sign up to set email alerts
|

Financial Impact of Third-Party Reimbursement Due to Changes in the Definition of ICD-9 Arthroscopy Codes 29880, 29881, and 29877

Abstract: Third-party reimbursement rates for cases in 2011 dropped by over 35% for similar cases in 2012. The percentage drop in Medicare payment has been similar to other payers, but the absolute reimbursements are lower. Codes 29875, 29876, and 29879 were used more often in 2012, but the absolute numbers do not balance the decrease in use of code 29877.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…It is unclear what drove this increase; however, it may be related to the relative value unit decrease for the 2 surgical CPT codes (29880 and 29881) used in the study. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear what drove this increase; however, it may be related to the relative value unit decrease for the 2 surgical CPT codes (29880 and 29881) used in the study. 10 …”
Section: Discussionmentioning
confidence: 99%
“…It is unclear what drove this increase; however, it may be related to the relative value unit decrease for the 2 surgical CPT codes (29880 and 29881) used in the study. 10 When compared with other surgical subspecialties, orthopaedic reimbursements have been reported to be declining at a greater rate. 11 Orthopaedic surgeons are being reimbursed less while balancing increased responsibilities tied to bundled payments, readmission penalties, and a multitude of quality metrics.…”
Section: Discussionmentioning
confidence: 99%
“…The results presented in these studies may have been impacted by the changes in reimbursement and billing practices following publication of the trial by Moseley et al In 2004, a non‐coverage determination was put forth by Medicare for the use of knee arthroscopy or debridement for knee OA [14]. While this initially may seem like it could deter the use of knee arthroscopy for degenerative conditions of the knee, a subsequent study suggested that it likely resulted in changes in coding to highlight alternative diagnoses, such as meniscal pathology rather than OA, and alternative procedures, such as synovectomy or meniscectomy rather than debridement of articular cartilage [8]. Therefore, these studies, which aimed to evaluate knee arthroscopy rates for the diagnosis of OA, may report a reduction in procedural rates that they are falsely attributing to the impact of Moseley's trial, rather than considering that it may instead reflect a change in procedural coding.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Medicare changed reimbursement for arthroscopic debridement by bundling code 29877 (debridement or shaving of articular cartilage) with 29880 (medial and lateral APM) and 29881 (medial or lateral APM) 29,30 . Reimbursement for meniscectomies with chondral debridement that would have been coded with 29877 has since decreased by 35%, but the impact of this coding change on the actual number of chondroplasties being performed with APM remains unknown 29 . A recent study also found that arthroscopic debridement is not cost-effective compared with nonoperative management of knee osteoarthritis 31 .…”
Section: Discussionmentioning
confidence: 99%